Novel Biodegradable Functional Amino Acid-Based Poly(ester Amide) Biomaterials: Design, Synthesis, Property and Biomedical Applications (Journal of Fiber Bioengineering and Informatics, 2012)
A new family of biodegradable and functional amino acid-based poly(ester amide)s (AA-PEAs) have beendesigned and synthesized as a new generation of biodegradable biomaterials for biomedical applications.This paper provides an overview of this new generation of biodegradable biomaterials, their designstrategy, synthesis, characterization, unique biological property and eventual biomedical applications.AA-PEAs are synthesized from 3 basic building blocks: amino acids, fatty diols and fatty diacids. Dueto the enormous variety of these 3 building blocks, a wide range of AA-PEAs could be tailor-designed formeeting specific clinical needs. These AA-PEAs have been engineered into a variety of physical formsranging from 3D microporous hydrogels, melt-spun fibers, electrospun fibrous membranes, films andmicrospheres. All these AA-PEAs have shown 2 unique biological properties: support natural woundhealing, and muted inflammatory response.
Keywords: Amino Acids; Poly(ester amide); Biodegradable; Inflammation; Synthesis; Biomaterials; Biomedical Applications; Fibrous Membrane; Electrospinning; Hydrogels; Microspheres; Fibers